Respectful maternity care in health centers of Addis Ababa city: a mixed method study - Amaha Haile Abebe; Rose Mmusi-Phetoe (BMC, 2022)
Abstract Objective The study aims to assess quality of obstetric and newborn care including respectfulness of the maternity care. Design The study used explanatory sequential mixed methods design . Setting This study was conducted in 50 health centres in Addis Ababa city administration January 25 to April 31, 2021. Methods During the quantitative phase 500 women in postpartum period were interviewed using structured questionnaire. In the second phase in-depth interview was conducted with 20 midwives and 13 health centre managers. The quantitative data was analysed using Statistical Package for Social Sciences (SPSS). The qualitative data was analysed using Colaizzi's seven step process. Results Only 24.6% of women had respectful maternity care (RMC). Only 46% of women had effective communication during child birth. Only 9.6% of women had emotional support during child birth. Majority of women were encouraged to mobilize, take food and be on labor position of their choice. However, only 22.4 and 18.8% of women respectively had a companion of choice and any pharmacologic pain relief during child birth. One in seven women (15%) had one form of disrespect and abuse during child birth. Conclusion Ensuring respectful maternity care needs strong policy direction to health facilities, public education on their right to respectful maternity care, training of care givers and monitoring care through engagement of frontline staff and clients.